Functional analysis of tick salivary serine and cysteine protease inhibitors - Kotál, Jan (Jihočeská univerzita, 2020)
The proposed thesis focuses on the characterization of two protease inhibitors present in tick saliva. More specifically, the thesis presents immunomodulatory properties, biochemical specificity and structure of a cysteine protease inhibitor named Iristatin. Another characterized protein, IRS-8, comes from a serpin family (serine protease inhibitors) and inhibits blood coagulation and complement system in the host. Furthermore, the thesis provides a literature overview and discussion of tick salivary molecules in the context of tick-host-pathogen interaction, vaccination potential and medicine potential. Two review manuscripts, which are part of this thesis summarize the effects of tick saliva and protease inhibitors on host immune mechanisms.
Functional analysis of tick salivary serine and cysteine protease inhibitors
Keywords: tick; saliva; immunity; coagulation; protease inhibitor; serpin; cystatin; tick; saliva; immunity; coagulation; protease inhibitor; serpin; cystatin